2017
DOI: 10.3389/fmicb.2017.01365
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing Reveals that Endoplasmic Reticulum Stress and Disruption of Membrane Integrity Underlie Dimethyl Trisulfide Toxicity against Fusarium oxysporum f. sp. cubense Tropical Race 4

Abstract: Fusarium wilt of banana, a destructive disease that affects banana production, is caused by Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4). In a previous study, we confirmed the strong inhibitory effects of Chinese leek (Allium tuberosum) on the incidence of this disease. Sulfur compounds are the primary antifungal constituents of Chinese leek. Among these, dimethyl trisulfide (DT) was the most abundant and exhibited the strongest inhibition of Foc TR4 growth and development. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The S. mutans strains were cultured overnight. The isolation, purification, and reverse transcription of total bacterial RNA into cDNA was performed as described previously (Zuo et al, 2017 ). qRT-PCR was performed using the Bio-Rad CFX96 system (Bio-Rad, Marnes-la-Coquette, France).…”
Section: Methodsmentioning
confidence: 99%
“…The S. mutans strains were cultured overnight. The isolation, purification, and reverse transcription of total bacterial RNA into cDNA was performed as described previously (Zuo et al, 2017 ). qRT-PCR was performed using the Bio-Rad CFX96 system (Bio-Rad, Marnes-la-Coquette, France).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that DMTS together with the volatiles from Chinese leek could inhibit conidial germination of Fusarium oxysporum f.sp. cubense tropical race 4 ( Foc TR4), and DMTS displayed the strongest inhibition among volatiles (Zhang et al, ; Zuo et al, , ). Moreover, DMTS together with the volatiles emitted from Streptomyces globisporus JK‐1 exhibited strong inhibitory effects on conidial germination of P. italicum and Botrytis cinerea , and DMTS acted as the main active compound (Li et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…DMTS has shown strong inhibitory effects on the growth of Penicillium italicum and Fusarium oxysporum f.sp. cubense tropical race 4 (Li et al, ; Zuo, Zhang, Chen, Chen, & Huang, ). However, the toxicity of DMTS to C. gloeosporioides has not been previously demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(A) mRNA was purified by using oligo(dT) magnetic beads and then digested into short fragments (approximately 200 bp). The RNA-Seq library preparation method were performed according to our previous method that was described by Zuo et al (2017) [26] and it included three replicates for each treatment. The amplified fragments were sequenced while using an Illumina HiSeq TM 2000.…”
Section: Methodsmentioning
confidence: 99%
“…PCR conditions were 95 °C for 15 min., followed by 40 cycles of 95 °C for 10 s, and annealing/extension at 60 °C for 30 s. The melting curve was determined for each sample. Relative gene expression was calculated while using the cycle threshold (Ct)2 −ΔΔCt method, as described by Zuo et al (2017) and Livak and Schmittgen (2001) [26,33]. Data from qRT-PCR analysis were expressed as means ±SD of three independent replicates.…”
Section: Methodsmentioning
confidence: 99%